GOOD PAYLOAD DEFORMATION FOR REVERSIBLE DATA HIDING IN MILITARY AND MEDICAL APPLCATION (International Journal of Engineering and Computer Science, 2017)
In reversible data hiding, the data value are modified by some rules and the exact data can be re-stored after the extraction of data on the receiver system. Here optimal rule value under payload criteria is done by using iterative algorithm .it calculates the estimated embedded image-original image.the estimated image are modified according to the optimal value transfer. The images are divided in to the subsets. A receiver was successfully able to extract and recover the original content in the subsets on inverse order. Hence good payload distortion can be achieved